A fast multipole accelerated BEM for 3-D elastic wave computation - Chaillat, Stéphanie; Bonnet, Marc; François Semblat, Jean- (European Journal of Computational Mechanics, 2008)
The solution of the elastodynamic equations using boundary element methods (BEMs) gives rise to fully-populated matrix equations. Earlier investigations on the Helmholtz and Maxwell equations have established that the Fast Multipole (FM) method reduces the complexity of a BEM solution to N log2 N per GMRES iteration. The present article addresses the extension of the FM-BEM strategy to 3D elastodynamics in the frequency domain. Efficiency and accuracy are demonstrated on numerical examples involving up to N = O(106) boundary nodal unknowns.